Grouting Mortars for Consolidation of Historical Renders Showing Loss of Adhesion - Tavares, M. (2010)
Grouting mortars for consolidation of historical renders showing loss of adhesion Martha Lins Tavares1, Mª Rosário Veiga2, Ana Fragata3 1Restorer, Laboratório Nacional de Engenharia Civil, Lisbon, Portugal, marthal@lnec.pt 2 Civil Engineer, Laboratório Nacional de Engenharia Civil, Lisbon, Portugal, rveiga@lnec.pt 3 Civil Engineer, Laboratório Nacional de Engenharia Civil, Lisbon, Portugal, afragata@lnec.pt Abstract - Loss of adhesion is one of the main forms of degradation of old renders, in the form of separation of different render layers or between render and substrate, producing anomalies, such as debonding, detachment, cracks and lacuna on the render. In the present paper a study developed at LNEC – National Laboratory of Civil Engineering of Portugal – is presented, concerning restoration techniques for historical renders by consolidation using grouts for adhesion restitution. Lime grouts for consolidation should be mechanically, physically and chemically compatible with the original render, as this is a practically irreversible treatment. The aim of the study was the discussion of characteristics of grouts, considering both compatibility and efficacy. Several grouting mortars are selected, the methodology of the study and the laboratory tests carried out are described, as well as the critical analysis of the results, and the conclusions are summarized. Some proposals for future research are also presented.